Heterozygous Che-1 KO mice show deficiencies in object recognition memory persistence. (6th October 2016) - Zalcman, Gisela; Corbi, Nicoletta; Di Certo, Maria Grazia; Mattei, Elisabetta; Federman, Noel; Romano, Arturo
Highlights: We generated a genetically modified Che-1 +/− KO mice. These mice are normal in its locomotor activity and anxiety behavior. These mice are normal in long-term memory formation. Che-1 +/− KO mice show deficits in object recognition memory persistence. Abstract: Transcriptional regulation is a key process in the formation of long-term memories. Che-1 is a protein involved in the regulation of gene transcription that has recently been proved to bind the transcription factor NF-κB, which is known to be involved in many memory-related molecular events. This evidence prompted us to investigate the putative role of Che-1 in memory processes. For this study we newly generated a line of Che-1 +/− heterozygous mice. Che-1 homozygous KO mouse is lethal during development, but Che-1 +/− heterozygous mouse is normal in its general anatomical and physiological characteristics. We analyzed the behavioral characteristic and memory performance of Che-1 +/− mice in two NF-κB dependent types of memory. We found that Che-1 +/− mice show similar locomotor activity and thigmotactic behavior than wild type (WT) mice in an open field. In a similar way, no differences were found in anxiety-like behavior between Che-1 +/− and WT mice in an elevated plus maze as well as in fear response in a contextual fear conditioning (CFC) and object exploration in a novel object recognition (NOR) task. No differences were found between WT and Che-1 +/− mice performance in CFC training and when tested at 24 h or 7 days after training. Similar performance was found between groups in NOR task, both in training and 24 h testing performance. However, we found that object recognition memory persistence at 7 days was impaired in Che-1 +/− heterozygous mice. This is the first evidence showing that Che-1 is involved in memory processes.